The importance of wild edible plant and macrofungi diversity to attain food security for the tribes of eastern India—a quantitative study - Mandal, Suman Kalyan; Saha, Sathi; Saha, Saradindu (Frontiers in Sustainable Food Systems, 2023)
Background Inventorization and promotion of traditionally used local flora can be a better option to gain a wide range of alternative edible resources and multiple nutritional benefits. A perusal of literature highlighted the poor nutritional status of the tribal community living in eastern India and pointed out the potential lack of information regarding locally available wild edible resources. Objective Present study aimed to document detailed information on wild edibles of eastern India, evaluate their cultural significance, and understand their role in achieving food security for the local tribes. Materials and methodology Traditional knowledge of wild edibles was collected using a semi-structured questionnaire. Standard protocols were followed for collecting data. The collected data were analyzed using specific statistical tools like Relative frequency of citation (RFC), and Cultural food significance index (CFSI) to identify the most cited and culturally significant species. Jaccard similarity index (JI) was used to check the similarity of food plant use in different localities and adjoining areas of the laterite region in eastern India. Results A total of 2,603 citations were made by the 153 participants for 83 types of wild edibles spread across 48 families. Among the 83 species, 65 species were angiosperms, three species were pteridophytes and the rest 15 were from fungal groups. The RFC value ranged from 0.04 to 0.76, and Madhuca longifolia (L.) J.F.Macbr. was identified as the most frequently cited species (FC = 116; RFC = 0.76). The Cultural food significance index (CFSI) value varied from 0.2 to 844, and thirteen wild edibles like Colocasia esculenta (L.) Schott, Enydra fluctuans Lour., Marsilea vestita Hook. & Grev., Termitomyces heimii Natarajan, etc. were identified as culturally most important in the locality. Conclusion Present study concludes that the local flora and macrofungi diversity is a treasure trove for fulfilling human hunger and gaining enough nutritional benefit. Scientific and sustainable utilization of these wild edibles can be a wise step to attain multiple health benefits and food security for the tribal community of eastern India. Moreover, culturally accepted species can be opted as a good source for bioprospecting nutraceuticals.